Mitonuclear incompatibility as a hidden driver behind the genome ancestry of African admixed cattle - Kwon, T.; Kim, K.; Caetano-Anolles, Kelsey; Sung, S.; Cho, S.; Jeong, C.; Hanotte, Olivier H.; Kim, H. (Springer, 2022)
Africa is an important watershed in the genetic history of domestic cattle, as two lineages of modern cattle, Bos taurus and B. indicus, form distinct admixed cattle populations. Despite the predominant B. indicus nuclear ancestry of African admixed cattle, B. indicus mitochondria have not been found on the continent. This discrepancy between the mitochondrial and nuclear genomes has been previously hypothesized to be driven by male-biased introgression of Asian B. indicus into ancestral African B. taurus. Given that this hypothesis mandates extreme demographic assumptions relying on random genetic drift, we propose a novel hypothesis of selection induced by mitonuclear incompatibility and assess these hypotheses with regard to the current genomic status of African admixed cattle.By analyzing 494 mitochondrial and 235 nuclear genome sequences, we first confirmed the genotype discrepancy between mitochondrial and nuclear genome in African admixed cattle: the absence of B. indicus mitochondria and the predominant B. indicus autosomal ancestry. We applied approximate Bayesian computation (ABC) to assess the posterior probabilities of two selection hypotheses given this observation. The results of ABC indicated that the model assuming both male-biased B. indicus introgression and selection induced by mitonuclear incompatibility explains the current genomic discrepancy most accurately. Subsequently, we identified selection signatures at autosomal loci interacting with mitochondria that are responsible for integrity of the cellular respiration system. By contrast with B. indicus-enriched genome ancestry of African admixed cattle, local ancestries at these selection signatures were enriched with B. taurus alleles, concurring with the key expectation of selection induced by mitonuclear incompatibility.Our findings support the current genome status of African admixed cattle as a potential outcome of male-biased B. indicus introgression, where mitonuclear incompatibility exerted selection pressure against B. indicus mitochondria. This study provides a novel perspective on African cattle demography and supports the role of mitonuclear incompatibility in the hybridization of mammalian species.